Hayat School Management in Facilitating Students’ Life-Long Learning Needs - Mardiani, Desika Putri; Nuryono, Wiryo; Kholidya, Citra Fitri; Windasari, windasari; Ningrum, Mallevi Agustin; Widya, Sherrin Nurlita (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
The desire to learn is a human nature, moreover, the complexity of learning needs in society is getting higher in this digital era which is aimed at meeting the needs of the time. Hayat School, a non-formal education institution rooted in divine values, facilitated education programs for students and the surrounding society. It starts from elementary school, society education, and vocational education that is conducted to fulfill their learning needs. This research aims to analyze the management of Hayat School in facilitating the life-long learning needs of Students and society and to describe the dimension of the enablers and barriers in the management. The research method used a qualitative approach with interviews, questionnaires, participation observation, and documentation as collection data techniques. The result is that Hayat School continues to make improvements to the managers, educators, and programs so they can manage creatively, some collaborations with local and international partners, and also involves surrounding society to participate in conducting society education comprehensively and make efforts in providing education programs for the community so they can be empowered and independent. Thus, Hayat School has managed a learning program that can meet the learning needs of students.